2022
DOI: 10.1039/d2nj02038f
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical deposition of ZnCo2O4/NiCo2S4 nanosheet arrays for high-performance supercapacitors

Abstract: The demand of power density has promoted the application of supercapacitors, and one hot study task for supercapacitors is high-energy-density electrode materials such as transition metal oxides or sulfides. Here,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…24 In addition, numerous studies have indicated that altering the micro/nanostructure and morphology of the ZCO electrode materials can significantly enhance their electrochemical performance. 8,17 Consequently, researchers have developed various synthesis methods, including hydro/solvothermal, 8 microwave-assisted, 17 sol–gel, 25 co-precipitation, 18,24 and electrodeposition 26 to produce a wide range of microstructures and morphological modifications, such as nanowires, 27 nanoflakes, 28 nanorods, 29 nanoparticles, 30 microspheres 24 and microflowers. However, there is still considerable scope for improving the morphological structure of ZCO material.…”
Section: Introductionmentioning
confidence: 99%
“…24 In addition, numerous studies have indicated that altering the micro/nanostructure and morphology of the ZCO electrode materials can significantly enhance their electrochemical performance. 8,17 Consequently, researchers have developed various synthesis methods, including hydro/solvothermal, 8 microwave-assisted, 17 sol–gel, 25 co-precipitation, 18,24 and electrodeposition 26 to produce a wide range of microstructures and morphological modifications, such as nanowires, 27 nanoflakes, 28 nanorods, 29 nanoparticles, 30 microspheres 24 and microflowers. However, there is still considerable scope for improving the morphological structure of ZCO material.…”
Section: Introductionmentioning
confidence: 99%
“…The ZCO/NCS composite electrodes were obtained through electrochemical deposition using a mixed solution of MOF-derived ZnCo 2 O 4 and precursors of Ni, Co, and S. A medium consisting of DMF and methanol was employed for the solvothermal synthesis of MOF-derived ZnCo 2 O 4 at 150 • C for 12 h. Subsequently, the synthesized material was treated with tannic acid and annealed at 600 • C for 2 h. The samples prepared under the electrodeposition condition (0.9 V, 10 min) exhibited a specific capacitance of 2385 F g −1 (at 1 A g −1 ) and a power density of 8.0 kW kg −1 at 10 A g −1 . Furthermore, a capacitance retention of 91.5% was observed after 5000 cycles [76].…”
Section: Solvothermal Synthesis Of Znco 2 Omentioning
confidence: 97%
“…11,12 Generally, the exploring of new electrode materials was considered the key for boosting the energy densities and increasing the voltage window of asymmetric supercapacitors (ASC). 13–15…”
Section: Introductionmentioning
confidence: 99%